Perlakuan Akuntansi Aset Biologis dan Akuntansi Produk Agrikultur Berdasarkan Psak 69 Pada Ud. Sri Pasuparata (Studi Kasus Di Desa Pasedahan, Kecamatan Manggis, Kabupaten Karangasem) - Erawan, Putu Adi; Julianto, I Putu (Universitas Pendidikan Ganesha, 2020)
This study aims to determine: (1) How to accounting for biological asset accounting for biological assets (laying hens) in the business of producing Sri Pasuparata chicken eggs based on PSAK 69 and, (2) How to accounting for agricultural products containing eggs based on PSAK 69 in business Sri Pasuparata. This research was conducted at the Pasuparata chicken egg production business, Pasedahan Village, Manggis District, Karangasem Regency. In this study using qualitative methods. The data used in this study are primary data and secondary data. The results of this study state that (1) biological asset accounting based on PSAK 69 does not yet have biological assets owned by Sri Pasuparata company, this relates to companies still using a very traditional way of increasing their business and human resources that are not in accordance with accounting needs. and (2) Accounting approval for agricultural products has not yet been approved. The company recognizes that the chicken eggs sold are still being considered in connection with the trade in goods with PSAK 69 that has been approved to obtain agricultural products produced from biological assets produced by the company.